Quality of Life and Its Predictive Factors Among Healthcare Workers After the End of a Movement Lockdown: The Salient Roles of COVID-19 Stressors, Psychological Experience, and Social Support - Woon, Luke Sy-Cherng; Mansor, Nor Shuhada; Mohamad, Mohd Afifuddin; Teoh, Soon Huat; Leong Bin Abdullah, Mohammad Farris Iman (Frontiers in Psychology, 2021)
Although healthcare workers play a crucial role in helping curb the hazardous health impact of coronavirus disease 2019 (COVID-19), their lives and major functioning have been greatly affected by the pandemic. This study examined the effects of the COVID-19 pandemic on the quality of life (QoL) of Malaysian healthcare workers and its predictive factors. An online sample of 389 university-based healthcare workers completed questionnaires on demographics, clinical features, COVID-19-related stressors, psychological experiences, and perceived social support after the movement lockdown was lifted. All domains of QoL were within the norms of the general population except for social relationship QoL, which was lower than the norm. Multiple linear regression analysis indicated that COVID-19-related stressors (e.g., stress due to annual leave being frozen, loss of daily routine, and frequent exposure to COVID-19 patients) and psychological sequelae (e.g., greater severity of depression, anxiety, and stress) predicted lower QoL. Conversely, greater perceived social support from friends and significant others predicted higher QoL. Clinical and demographic characteristics predicted QoL to a lesser extent: A history of pre-existing medical illness was associated only with lower physical health QoL, whereas older age and being single, divorced, or widowed were only predictive of higher environmental QoL. Efforts to enhance QoL among healthcare workers in response to the pandemic should focus on mitigating COVID-19-related stressors and psychological sequelae and facilitating social support.